Banking crises: An equal opportunity menace - Reinhart, Carmen M.; Rogoff, Kenneth S. (Journal of Banking & Finance, 2013)
The historical frequency of banking crises is similar in advanced and developing countries, with quantitative parallels in both the run-ups and the aftermath. We establish these regularities using a dataset spanning from the early 1800s to the present. Banking crises weaken fiscal positions, with government revenues invariably contracting. Three years after a crisis central government debt increases by about 86%. The fiscal burden of banking crisis extends beyond the cost of the bailouts. We find that systemic banking crises are typically preceded by asset price bubbles, large capital inflows and credit booms, in rich and poor countries alike.